Conceptual framework for linkages and partnerships in BIMSTEC - Roy, Devesh; Pradhan, Mamata; Boss, Ruchira; Rashid, Shahidur (International Food Policy Research Institute, 2022)
The Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation (BIMSTEC) is a regional organization which came into being in 1997. It comprises seven member states: five from South Asia, namely, Bangladesh, Bhutan, India, Nepal, and Sri Lanka, and two from Southeast Asia, Myanmar and Thailand. BIMSTEC region is home to around 1.5 billion people, that is, nearly 22 percent of the global population with a combined gross domestic product (GDP) of US$2.7 trillion.